Total Phenolic Content and Antioxidant Activity of Two Teucrium Species from Syria - Reem Ghassan Alali ,; Mays Rizk Khazem, (Journal of Pharmacy and Nutrition Sciences, 2020)
Germander (Teucrium, Lamiaceae) is a genus commonly used as a medicinal herb in the middle east. The aim of this study was to estimate total polyphenols and antioxidant activity of different extracts from two Syrian Teucrium species (Teucrium polium and Teucrium creticum). Total polyphenols content was measured using Folin-Ciocalteu assay and the antioxidant activity was evaluated in vitro by DPPH assay (free radical scavenging activity against 1, 1 –diphenyl-2-picrylhydrazyl). The total polyphenols content and antioxidant activity of T. creticum extracts were higher than T. polium ones. Phenols contents ranged from 16.388 to 105.672 mg GA E/ g dry weight extract. The extracts showed significant scavenging activity against DPPH, with IC50 values ranging between 0.195 and 0.710 mg/ml. The methanolic extracts show higher antioxidant activity from the two species. A good correlation between DPPH scavenging activities and contents of polyphenols was found. These results show that Syrian Teucrium species, especially T. creticum least Known among all, is a rich source of phenols and natural antioxidant compounds, that can be used as a natural food preservative.